2012
DOI: 10.4161/epi.20733
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1-mediated deacetylation of MeCP2 contributes to BDNF expression

Abstract: Methyl-CpG binding protein 2 (MeCP2) binds methylated cytosines at CpG sites on DNA and it is thought to function as a critical epigenetic regulator. Mutations in the MeCP2 gene have been associated to Rett syndrome, a human neurodevelopmental disorder. Here we show that MeCP2 is acetylated by p300 and that SIRT1 mediates its deacetylation. SIRT1, the mammalian homologue of Sir2 in yeast, is a nicotinamide-adenine dinucleotide (NAD+)-dependent histone deacetylase that belongs to the family of HDAC class III si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 32 publications
(47 reference statements)
2
101
0
1
Order By: Relevance
“…SIRT1 has also been demonstrated to deacetylate methyl-CpG-binding protein 2 (MeCP2). Deacetylated MeCP2 is released from methylated CpG sites within the brain-derived neurotrophic factor promoter, thus leading to increased expression of brainderived neurotrophic factor, a known neuroprotective protein [46]. SIRT1 may also regulate a neuroprotective phenotype through the deacetylation and thus activation or inhibition of transcription factors, transcriptional co-activators, and nuclear receptors [37].…”
Section: Acetylationmentioning
confidence: 99%
“…SIRT1 has also been demonstrated to deacetylate methyl-CpG-binding protein 2 (MeCP2). Deacetylated MeCP2 is released from methylated CpG sites within the brain-derived neurotrophic factor promoter, thus leading to increased expression of brainderived neurotrophic factor, a known neuroprotective protein [46]. SIRT1 may also regulate a neuroprotective phenotype through the deacetylation and thus activation or inhibition of transcription factors, transcriptional co-activators, and nuclear receptors [37].…”
Section: Acetylationmentioning
confidence: 99%
“…This suggested a potential mechanism (regulation of gene expression by neuronal activity) by which MeCP2 mutation could lead to the developmental abnormalities observed in neurons [117,118]. Recently, it was shown that MeCP2 is acetylated by p300 and that SIRT1 mediates its deacetylation [119]. This suggests a functional interplay between 2 critical epigenetic regulators, MeCP2 and SIRT1, modulating MeCP2 binding to the BDNF promoter in specific brain regions.…”
Section: Mecp2 Duplication Syndromementioning
confidence: 99%
“…It would be intriguing to investigate such mechanisms directly after nerve injury where calcium-dependent depolarization occurs. Promoter binding of MECP2 to the Bdnf promoter can also be regulated by acetylation and deacetylation via the histone modifying enzymes EP300 and SIRT1, respectively [75], or by phosphorylation [76]. Surprisingly, binding of MECP2 was also reported earlier to repress Bdnf expression, depending on the specific promoter region likely regulating the expression of selected BDNF isoforms [77,78].…”
Section: Dna Methylation In Neuronal Plasticity and Axonal Injurymentioning
confidence: 99%